Disc Battery-The escalating risk of ingestion by children in IraqAnd subsequent clinical events and complications. - Jabir, Sabah , N.; Al-Assal, Muthana D. ,; Mohammed, Ahmed . , A (AL-Kindy College Medical Journal, 2013)
Background: Disc battery ingestion is a common serious problem in Iraq. It increase in the last years because of the increase in number of electronic toys that uses these batteries. These batteries contains many types of irritant chemicals that increases the risk of it’s ingestion. Methods:We reviewed the medical records of children aged between 1year and 7 years old admitted to Surgical Specialty Hospital/Baghdad Medical City due to disc battery ingestion from January 2007 through December 2010). The diagnosis of disc battery ingestion was based upon history, clinical symptoms, and results of imaging studies. The clinical data reviewed included sex, age, clinical manifestation and duration of symptoms, hospital course, imaging findings, and endoscopic results. Results: 50 patients were admitted to Thoracic and vascular Department/Surgical Speciality Hospital/Baghdad Medical city Complex (26 males and 24 females) of disc battery ingestion with a mean age of 1.873 years (range, 7 months to 7 years). Fourty one patients had Symptoms of Dysphagia, vomiting, nausea, and abdominal pain. Four cases with no history of disc battery ingestion and were accidentally found by X ray studies. Two patients complained from Aspiration and chalking, two patients had mediastinitis and died at later on due to sepsis, and only one case had surgical emphysema. Thirty-eight cases had their batteries impacted in the upper esophagus and Nine cases had their batteries impacted in mid-esophagus, and Three cases had their battery impacted in the lower-